Effects of methanolic extracts from edible plants on endogenous secretory receptor for advanced glycation end products induced by the high glucose incubation in human endothelial cells - Yoshinori Okada; Mizue Okada (Wolters Kluwer Medknow Publications, 2015)
Background: In diabetic populations, endogenous secretory receptor for advanced glycation end products (esRAGE) levels may be related to the degree of diabetic complications or to the protection from diabetic complications. Objective: We investigated the impact of 29 methanolic extracts from edible plants on esRAGE production in human umbilical vein endothelial cells (HUVECs) cultured in high (4.5 g/L) glucose. Materials and Methods: Edible plants were minced, and extracts were obtained with methanol overnight. The methanolic extracts from 29 edible plants were evaporated in a vacuum. For screening study purposes, HUVECs were seeded in culture dishes (1.5 × 10 5 cells). Then, HUVECs were incubated with 1 g/L or 4.5 g/L of glucose in SFM CS-C medium treated with methanolic extracts from edible plants (MEEP) for 96 h. Determination of esRAGE production in the cell culture-derived supernatants was performed by colorimetric ELISA. The 8-hydroxydeoxyguanosine (8-OHdG) level was determined by using the 8-OHdG Check ELISA kit. Peroxynitrite-dependent oxidation of 2', 7'- dichlorodihydrofluorescein to 2', 7'-dichlorofluorescein was estimated based on the method described by Crow. Because MEEP were methanolic extracts, we measured their total phenolic content (TPC). TPC was measured with a modified version of the Folin-Ciocalteu method. Results: The results showed eight extracts increased esRAGE production. The extract from white radish sprouts showed the highest esRAGE production activity, and then eggplant, carrot peel, young sweet corn, Jew's marrow, broad bean, Japanese radish and cauliflower. In order to understand the mechanism of esRAGE production, the eight extracts were examined for DNA damage, peroxynitrite scavenging activity, and TPC in correlation with their esRAGE production. The results showed esRAGE production correlates with the peroxynitrite level and TPC. Conclusion: This study supports the utilization of these eight extracts in folk medicine for improved treatment of diabetic complications.